La virtud: la recta razón en el profesional que experimenta con animales. (2013)
Virtue according to Aristotle s thought is a medium term with regard to us regulated by right reason; as a prudent man. would act. It is that mode of being by which man becomes good and through which he performs his function very well. Virtue is directly related to how people act, these steps or actions should lead to a good; and that good must be a generator of happiness in man. It depends just on man himself that the actions he performs are done well and according to virtue. Thus; it is expected that the scientist who experiments with animals to act according to virtue; to have a permanent disposition to work according to right reason; and to discuss what is good; particularly what does good especially to other forms of life which share with us the mystery of life. The Aristotelian virtuous man must search that his actions are mediated by reason to choose what is good ; not for himself but for the common good.